LARS2 DNA methylation predicts the prognosis in colon cancer - Yingzhou Fu; Wei Xie; Qifan Ren; Jiao Wu; Ying Long; Ying Liu (Scientific Reports)
Abstract Colon cancer is a highly aggressive solid tumor. Because most studies have focused on the intrinsic oncogenic pathways of tumors, we focused on the relationship between DNA methylation genes in the tumor immune microenvironment and colon cancer prognosis. We download RNA-seq data from the TCGA dataset. DNA methylation genes were scored using the GSVA method, and this score was subjected to GSEA, GO and KEGG enrichment analysis. Then, in vitro experiments examined the effect of silencing LARS2 on the proliferation and apoptosis of HCT116 cells. We obtained 2635 genes, 144 were obtained after single factor screening, and 8 genes were obtained through random forest dimensionality reduction. They are LARS2, TEX2, BRIP1, QSOX2, HOOK1, COX19, NEK4 and STXBP4. Survival analysis indicated that patients with high Riskscore had poor prognosis. There were significant differences in the expression of DNA methylation genes between the two groups with high and low Riskscore. The immune checkpoints of different Riskscore groups include Antigen present, Ligand, Receptor, Co-inhibitor, Co-stimulator, Other, and Cell adhesion. There were significant differences in the expression of genes and DNA integrity checkpoint, histone deacetylation, mitotic DNA damage checkpoint, TGF-beta signaling pathway, Platinum drug resistance and Protein processing in endoplasmic reticlum pathway at the level of Antigen present. Silencing of LARS2 decreased the proliferative capacity and increased the apoptosis rate of HCT116. Our findings suggest that LARS2 methylation could affects colon cancer development.